2022
DOI: 10.6002/ect.2020.0526
|View full text |Cite
|
Sign up to set email alerts
|

Management of COVID-19 in Liver Transplant Recipients With Immunosuppressant Therapy: Experiences of an Iranian Transplant Registry

Abstract: Background: Following the pandemic of COVID-19 and the increased COVID-19 risk in transplant patient receptions, the authors assessed the prevalence, clinical course, and the outcome of the COVID-19 infection among liver transplant receptions. Methods: By designing and the use of researcher made questionnaire and the use of medical services, liver transplantation recipients under our center surveyed in terms of COVID-19 infection.Results: Seven patients infected with COVID-19 were identi ed from 265 liver tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…For fear of organ rejection, the patients’ immunosuppressive regimens were only slightly modified, with mycophenolate mofetil (MMF) dose being reduced to limit liver enzyme level elevation. While previous studies have argued in favor of lowering immunosuppression during COVID-19, Sheikhalipour et al [ 21 ], among others, have shown that despite minimal alterations in the patients’ immunosuppressive regimen, most participants fully recovered from COVID-19[ 22 ]. Ethical considerations regarding the risk of acute rejection following a significant reduction in the immunosuppressive regimen make randomized control trials investigating the role of immunosuppression discontinuation or decrease in the setting of COVID-19 inherently challenging.…”
Section: Immunosuppression and Covid-19 In Liver Transplant Recipientsmentioning
confidence: 99%
“…For fear of organ rejection, the patients’ immunosuppressive regimens were only slightly modified, with mycophenolate mofetil (MMF) dose being reduced to limit liver enzyme level elevation. While previous studies have argued in favor of lowering immunosuppression during COVID-19, Sheikhalipour et al [ 21 ], among others, have shown that despite minimal alterations in the patients’ immunosuppressive regimen, most participants fully recovered from COVID-19[ 22 ]. Ethical considerations regarding the risk of acute rejection following a significant reduction in the immunosuppressive regimen make randomized control trials investigating the role of immunosuppression discontinuation or decrease in the setting of COVID-19 inherently challenging.…”
Section: Immunosuppression and Covid-19 In Liver Transplant Recipientsmentioning
confidence: 99%